LOCAL WISDOM OF BADUY INDIGENOUS COMMUNITY IN ENVIRONMENTAL CONSERVATION EFFORTS FOR CHARACTER EDUCATION DEVELOPMENT IN ELEMENTARY SCHOOLS - Hendracipta, Nana; Hufad, Achmad; Leksono, Suroso Mukti (JPSD (Jurnal Pendidikan Sekolah Dasar), 2023)
This research aims to describe the local knowledge of the Baduy indigenous community in environmental conservation efforts, then describe the values of local wisdom of the Baduy community in environmental conservation efforts, and finally, describe the values of local wisdom of the Baduy indigenous community concerning the development of character education in elementary schools. The research method used is qualitative descriptive with data collection techniques such as interviews, documentation, and observations. The research results show that local knowledge and the values of local wisdom of the Baduy indigenous community are formed due to the interaction between the Baduy indigenous community and the geographical and topographical conditions of their natural environment in the Kendeng Mountains. The local knowledge of the Baduy indigenous community concerning environmental conservation includes knowledge about conservation zones, including settlement zones, cultivation zones, and conservation forest zones. The Baduy indigenous community is also familiar with various types of forests, such as cultivated, protected, and conservation forests. The values of local wisdom of the Baduy indigenous community concerning environmental conservation include not polluting rivers, not indiscriminately cutting down trees, the obligation to use natural resources for livelihood, the obligation to reforest barren land, the obligation to preserve water sources, not damaging mountains and valleys, the obligation to leave everything in nature as it is, and the value of honesty. Furthermore, the values that can be cultivated through character education in elementary schools include values for preserving and conserving natural resources and the value of honesty in utilizing natural resources.